Safety and immunogenicity of CpG 1018 and aluminium hydroxide-adjuvanted SARS-CoV-2 S-2P protein vaccine MVC-COV1901: interim results of a large-scale, double-blind, randomised, placebo-controlled phase 2 trial in Taiwan. Issue 12 (December 2021) - Hsieh, Szu-Min; Liu, Ming-Che; Chen, Yen-Hsu; Lee, Wen-Sen; Hwang, Shinn-Jang; Cheng, Shu-Hsing; Ko, Wen-Chien; Hwang, Kao-Pin; Wang, Ning-Chi; Lee, Yu-Lin; Lin, Yi-Ling; Shih, Shin-Ru; et al.
Summary: Background: MVC-COV1901, a recombinant protein vaccine containing pre-fusion-stabilised spike protein S-2P adjuvanted with CpG 1018 and aluminium hydroxide, has been shown to be well tolerated with a good safety profile in healthy adults aged 20–49 years in a phase 1 trial, and provided a good cellular and humoral immune responses. We present the interim safety, tolerability, and immunogenicity results of a phase 2 clinical trial of the MVC-COV1901 vaccine in Taiwan. Methods: This is a large-scale, double-blind, randomised, placebo-controlled phase 2 trial done at ten medical centres and one regional hospital in Taiwan. Individuals aged 20 years or older who were generally healthy or had stable pre-existing medical conditions were eligible for enrolment. Exclusion criteria included (but were not limited to) travel overseas within 14 days of screening, intention to travel overseas within 6 months of the screening visit, and the absence of prespecified medical conditions, including immunosuppressive illness, a history of autoimmune disease, malignancy with risk to recur, a bleeding disorder, uncontrolled HIV infection, uncontrolled hepatitis B and C virus infections, SARS-CoV-1 or SARS-CoV-2 infections, an allergy to any vaccine, or a serious medical condition that could interfere with the study. Study participants were randomly assigned (6:1) to receive two doses of either MVC-COV1901 or placebo, administered via intramuscular injection on day 1 and day 29. MVC-COV1901 contained 15 μg of S-2P protein adjuvanted with 750 μg CpG 1018 and 375 μg aluminium hydroxide in a 0·5 mL aqueous solution, and the placebo contained the same volume of saline. Randomisation was done centrally by use of an interactive web response system, stratified by age (≥20 to <65 years and ≥65 years). Participants and investigators were masked to group assignment. The primary outcomes were to evaluate the safety, tolerability, and immunogenicity of MVC-COV1901 from day 1 (the day of the first dose) to day 57 (28 days after the second dose). Safety was assessed in all participants who received at least one dose. Immunogenicity was assessed by measuring geometric mean titres (GMTs) and seroconversion rates of neutralising antibody and antigen-specific IgG in the per-protocol population. This study is registered with ClinicalTrials.gov, NCT04695652 . Findings: Of 4173 individuals screened between Dec 30, 2020, and April 2, 2021, 3854 were enrolled and randomly assigned: 3304 to the MVC-COV1901 group and 550 to the placebo group. A total of 3844 participants (3295 in the MVC-COV1901 group and 549 in the placebo group) were included in the safety analysis set, and 1053 participants (903 and 150) had received both doses and were included in the per-protocol immunogenicity analysis set. From the start of this phase 2 trial to the time of interim analysis, no vaccine-related serious adverse events were recorded. The most common solicited adverse events in all study participants were pain at the injection site (2346 [71·2%] of 3295 in the MVC-COV1901 group and 128 [23·3%] of 549 in the placebo group), and malaise or fatigue (1186 [36·0%] and 163 [29·7%]). Fever was rarely reported (23 [0·7%] and two [0·4%]). At 28 days after the second dose of MVC-COV1901, the wild-type SARS-CoV-2 neutralising antibody GMT was 662·3 (95% CI 628·7–697·8; 408·5 IU/mL), the GMT ratio (geometric mean fold increase in titres at day 57 vs baseline) was 163·2 (155·0–171·9), and the seroconversion rate was 99·8% (95% CI 99·2–100·0). Interpretation: MVC-COV1901 has a good safety profile and elicits promising immunogenicity responses. These data support MVC-COV1901 to enter phase 3 efficacy trials. Funding: Medigen Vaccine Biologics and Taiwan Centres for Disease Control, Ministry of Health and Welfare.